Assessing the impacts of phosphorus inactive clay on phosphorus release control and phytoplankton community structure in eutrophic lakes. (December 2016) - Su, Yuping; Zhang, Chaowei; Liu, Jianxi; Weng, Yuan; Li, Helong; Zhang, Dayi
Abstract: Addressing the challenge that phosphorus is the key factor and cause for eutrophication, we evaluated the phosphorus release control performance of a new phosphorus inactive clay (PIC) and compared with Phoslock ® . Meanwhile, the impacts of PIC and Phoslock ® on phytoplankton abundance and community structure in eutrophic water were also discussed. With the dosage of 40 mg/L, PIC effectively removed 97.7% of total phosphorus (TP) and 98.3% of soluble reactive phosphorus (SRP) in eutrophic waters. In sediments, Fe/Al-phosphorus and organic phosphorus remained stable whereas Ca-phosphorus had a significant increase of 13.1%. The results indicated that PIC may form the active overlay at water-sediment interface and decrease the bioavailability of phosphorus. The phytoplankton abundance was significantly reduced by PIC and decreased from (1.0–2.4) × 10 7  cells/L to (1.3–4.3) × 10 6  cells/L after 15 d simultaneous experiment. The phytoplankton community structure was also altered, where Cyanobacteria and Bacillariophyceae were the most inhibited and less dominant due to their sensitivity to phosphorus. After PIC treatment, the residual lanthanum concentration in water was 1.44–3.79 μg/L, and the residual aluminium concentration was low as 101.26–103.72 μg/L, which was much less than the recommended concentration of 200 μg/L. This study suggests that PIC is an appropriate material for phosphorus inactivation and algal bloom control, meaning its huge potential application in eutrophication restoration and management. Graphical abstract: Highlights: Phosphorus inactivation clay for effective phosphorus immobilization. Over 97.7% and 98.3% removal efficiency for total and soluble active phosphorus. Strongly inhibit phytoplankton from (1.0–2.4) × 10 7  cells/L to (1.3–4.3) × 10 6  cells/L. Significantly alter phytoplankton community structure. Low La (<3.79 μg/L) and Al (<104.09 μg/L) residue for drinking water safety. Abstract : Phosphorus inactive clay effectively immobilizes phosphorus in eutrophic waters, forms active overlay for 15-day phosphorus release control, and inhibits algal bloom.